Digitizing Web-Based Village Profiles as a Means of Historical Preservation and Promoting Local Potential in Matobe Village, Mentawai - Arda Decs’ta Heri Putri; May Sandra Putri; Intan SepriYelmi; Muhammad Gians Abdul Ghani; Fajar Anugrah; Zulhendra (PT. TAKAZA INNOVATIX LABS, 2026)
The development of village digitalization policies in Indonesia has not been fully followed by the availability of official information media at the village level, including in Matobe Village, which has a rich history, MSMEs, tourism potential, and tsunami vulnerability. This research/community service aims to develop a Matobe Village profile website as a means of preserving local history, promoting economic and tourism potential, and disaster education. The study uses a descriptive qualitative approach in the form of community-based research development. The population includes village government, community leaders, MSME actors, tourism managers, and residents in coastal areas; the sample was selected purposively, focusing on key informants who understand history, MSMEs, tourism, and disaster risk. The main instruments were researchers and a team of students, supported by interview guidelines, observation sheets, visual documentation, and GPS. Data were collected through observation, in-depth interviews, documentation, and participatory mapping; analysis was conducted thematically with triangulation of sources and methods. The results of the study show the realization of the desamatobe.site website that contains documented local history, a MSME directory, tourism information on the Nipah Forest and Mabola Waterfall, as well as a digital map of tsunami-prone areas and zones. In conclusion, the village profile website plays a strategic role as a medium for historical preservation, promoting local potential, increasing information transparency, and strengthening the digital literacy capacity and disaster preparedness of village communities.